Health Care Professionals' Perception of Stress During COVID-19 Pandemic in Iran: A Qualitative Study - Rouhbakhsh, Ashraf; Badrfam, Rahim; Nejatisafa, Ali-Akbar; Soori, Marzieh; Sharafi, Sayedeh Elham; Etesam, Farnaz; Shahmansouri, Nazila; Arbabi, Mohammad; Noorbala, Ahmad Ali (Frontiers in Psychiatry, 2022)
Abstract Background: The health care professionals have a unique role in controlling the pandemic of COVID-19 and decreasing its mortality and morbidity. The burden of care and psychological impact of working in this circumstance can be unfavorable for many caregivers. In this qualitative study, the health care professionals’ perception of stress during COVID-19 pandemic in Iran was assessed and several implications were proposed. Materials and Methods: The participants were selected among staff who were providing medical services to patients with COVID-19 infection at the largest teaching hospital in Iran. Quota sampling was used to include physicians, nurses, and other paramedics. The grounded theory was selected to develop interview questions. Moreover, the thematic approach was applied to analyze the data content and data analysis was performed based on open and axial coding following the implementation of codes in MAQDA software. Results: A wide range of psychological reactions including anxiety, feelings of guilt, depression, and anger were detected in the staff. Uncertainty accompanied by the pandemic of COVID-19 and shortcomings in preparation for crisis management were recognized as the two main sources of stress among health care professionals. Conclusion: Based on the findings of the study, it is important to identify and evaluate the mental health needs of healthcare professionals. To reduce stress among health staff at COVID-19 care centers, it seems that the optimal strategy is simultaneous improvement in equipment and crisis management.